The Effect of Consumption of Dried Spinach (Spinacia oleracea) on Level of Hemoglobin and Uric Acid for Sample of Women. - Baghdad Science Journal (Baghdad Science Journal, 2015)
This study been conducted and applied in Alrashed Health Center/Mahmodia Sector/ kerigh Sector/Ministry of Health/Baghdad City, and conducted on samples of women who are suffering from iron deficiency (Hemoglobin%) in blood for the year 2013. Fifty women been selected (married, unmarried), their ages ranging between 19-40 years old, they been given dried grinding spinach tablet. The dose been given was 3 tablet/day/4-6 weeks, after taken the percentage of Hemoglobin and Uric acid for all studied samples before and after dried spinach tablet given. It was appeared from samples analysis primarily and statically for 50 women, that 4% upon them only suffering high Iron deficiency (8.0-9.9 mg/100ml), 38% upon them suffering from middle iron deficiency (9.0-9.9 mgl/100ml), 46% upon them who suffering from little blood Iron deficiency (10.0-10.9 mgl100ml), and only 12% % upon them who suffering from slight blood Iron deficiency (11.0-11.9 mg/100ml). Also it was appeared that none of the women suffering from high level of Uric acid in their blood.The results of the experiment declare a significant difference due to the dose of tablets dried Spinach (3 tablet/day/ 4-6 weeks), which increase the percentage of Hemoglobin in the blood by 1-1.5 degree/ week and reached the optimum percentage 12 degree and up in 4-6 weeks, with no acidity, and the undesirable test which using the medicine (Ferro-Folic tablets). Although of the above, taking of Spanish tablets doesn't effect on much increasing the percentage of Uric acid, but in small percentage and all of it lower than the normal percentage which is (7.3 mg/100ml).From all of the above we can conclude, that we are able to manufacture the grinded dried Spinach tablet and to be used as medicine to treat Iron deficiency cases and to be given to pregnant women especially in the first three months of pregnancy, due to the disability of taken the chemical medicine, due to the probable distortion happen for the fetus, and also to the individuals who are suffering from Hemolytic anemia. So, for all the above facts, this type of studies and researches should be supported and encouraged the National medicine products against the imported chemical medicine.